2015
DOI: 10.15252/embj.201488044
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the transition zone by Mks5/Rpgrip1L establishes a ciliary zone of exclusion (CIZE) that compartmentalises ciliary signalling proteins and controls PIP2 ciliary abundance

Abstract: Cilia are thought to harbour a membrane diffusion barrier within their transition zone (TZ) that compartmentalises signalling proteins. How this "ciliary gate" assembles and functions remains largely unknown. Contrary to current models, we present evidence that Caenorhabditis elegans MKS-5 (orthologue of mammalian Mks5/Rpgrip1L/Nphp8 and Rpgrip1) may not be a simple structural scaffold for anchoring > 10 different proteins at the TZ, but instead, functions as an assembly factor. This activity is needed to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
219
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(238 citation statements)
references
References 85 publications
(199 reference statements)
18
219
1
Order By: Relevance
“…The ciliary membrane is continuous with the cell body plasma membrane, but the transition zone at the ciliary base functions as a diffusion barrier and selective gate for the passage of soluble and membrane-bound components into and out of the ciliary compartment, thereby endowing cilia with a unique protein and lipid composition ( Figure 1A) [15][16][17][18]. In many cell types and organisms, such as Trypanosoma and mammalian fibroblasts, the proximal region of the cilium is surrounded by a cytoplasmic invagination of the periciliary membrane, known as the ciliary pocket (CiPo; Figures 1A and 2), which serves as a hotspot for exo-and endocytosis of vesicles for the delivery and retrieval of ciliary membrane components [19].…”
Section: Primary Cilia: Master Coordinators Of Cellular Signaling Patmentioning
confidence: 99%
See 1 more Smart Citation
“…The ciliary membrane is continuous with the cell body plasma membrane, but the transition zone at the ciliary base functions as a diffusion barrier and selective gate for the passage of soluble and membrane-bound components into and out of the ciliary compartment, thereby endowing cilia with a unique protein and lipid composition ( Figure 1A) [15][16][17][18]. In many cell types and organisms, such as Trypanosoma and mammalian fibroblasts, the proximal region of the cilium is surrounded by a cytoplasmic invagination of the periciliary membrane, known as the ciliary pocket (CiPo; Figures 1A and 2), which serves as a hotspot for exo-and endocytosis of vesicles for the delivery and retrieval of ciliary membrane components [19].…”
Section: Primary Cilia: Master Coordinators Of Cellular Signaling Patmentioning
confidence: 99%
“…As we discuss in a later section of this intraflagellar transport (IFT), and trafficking processes that control ciliary assembly and targeting of receptors to the ciliary membrane. The ciliary membrane (red) is enriched in PI(4)P whereas PI(4,5)P 2 is abundant in the periciliary membrane [18,106,107]. (B) Images of primary cilia (arrows) analyzed by scanning electron microscopy of renal proximal tubule epithelial cells (left image reproduced, with permission, from [108]) and by immunofluorescence microscopy of mouse embryonic fibroblasts using anti-ARL13B (cyan) to mark the cilium, which lies in close proximity to the Golgi (anti-giantin, green) and the nucleus (DAPI, blue) (right image).…”
Section: The Ciliary Pocket: a Specialized Site For Endo-and Exocytosismentioning
confidence: 99%
“…Retinitis pigmentosa GTPase regulator-interacting protein-1 like (RPGRIP1L), located <100 bp upstream and in opposite transcriptional orientation to FTO ( Figure 1A), is a transition zone structural component of the primary cilium (16), an organelle implicated in human energy homeostasis (17). We have shown that the obesity-protective allele at FTO intronic SNP rs8050136 promotes the DNA-binding of the cut-like homeobox 1 (CUX1) isoform P110 that acts as an activator of FTO and RPGRIP1L expression in vitro (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The ciliary axoneme is anchored by the centriolederived basal body, and is ensheathed by the ciliary membrane. Located between the basal body and axoneme, the transition zone forms a diffusion barrier that modulates the selective passage of proteins to and from the cilium [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%